Konstruksi Realitas Sosial:Pemikiran Peter L. Berger Tentang Kenyataan Sosial - Ferry Adhi Dharma (Universitas Muhammadiyah Sidoarjo, 2018)
Peter Ludwing Berger is a productive sociologist, especially in the study of the sociology of knowledge. Learning a lot from his teacher, Alfred Schutz, made Berger loudly reject the idea of ​​positivism which for him was more or less inhumane compared to the flow of phenomenology. Through the concept of sociology, Berger's knowledge sees reality as two: objective and subjective. Berger agrees with Karl Marx's anthropological presupposition about the objective reality of humans as a socio-cultural product, however, in the subjective reality, human beings are organisms that have certain tendencies in society and are interpretive. To understand what is real for society, Berger formulates his theory of reality construction in three stages: externalization, objectification, and internalization.